Estimation of Porosity and Permeability by using Conventional Logs and NMR Log in Mishrif Formation/Buzurgan Oil Field - Al-Janaee, Hiba M.; Al-shahwan, Muwafaq F. (Journal of Petroleum Research and Studies, 2019)
Permeability and porosity values regarded as important fundamentals in the petroleum studies and researches especially for the interests in the reservoir topics, many methods and tools were founded for this purpose from time to time. The modern log technology one of this tools but consumes more time and financial possibilities in addition to the experts, such as Nuclear Magnetic Resonance Tools which considered one of the unconventional logs, so that, for this it was necessary to find a method to get the permeability and porosity values for the NMR log by using the conventional logs, note that it has been confirmed the modern studies the high accuracy and reliability for the NMR permeability and NMR porosity. Because the importance of this values , this study deals with the possibility of get these values from the conventional logs with these from NMR log, because of ease dealing with conventional logs and ease of getting it. After making the data analyses and processing this study results that led to putting many transformation formulas which give high correlations to high accuracy applying for this values in the researching and applying aspects and relating with reservoir prediction and modeling which connecting with drilling and producing works. The carbonate Mishrif Fm. In the Buzurgan oil field was selected to achieve this study by chose four oil production wells(Bu-40, Bu-51, Bu-52) in the south and north domes, in the future facilitate the prediction ways for any well has been logged by the open hole logs.